Bayesian Modeling Competitions for the Classroom - Berg, Arthur (Revista Colombiana de Estadística, 2021)
Three educational and engaging competitions are described for students studying Bayesian statistics. These competitions are designed to help students explore the topics of James-Stein estimation, the German tank problem, and resampling inference. These competitions will inspire students to think creatively, challenge students to develop effective Bayesian models, and motivate students to pursue excellence in competition with their peers. The competition structures can be easily adapted for use in introductory or advanced Bayesian statistics courses.